Use of omentum flap for induction of free skin graft healing - Pascoli, A. L. [UNESP]; Reis Filho, N. P. [UNESP]; Ferreira, M. G.P.A. [UNESP]; Viéra, R. B. [UNESP]; Negrão, S. L.; Yamada, D. I. [UNESP]; Magalhães, G. M.; Uscategui, R. A.R. [UNESP]; Barata, J. S. [UNESP]; Laus, J. L. [UNESP]; De Nardi, A. B. [UNESP] (FapUNIFESP (SciELO), 2022)
The objective of this study was to assess healing induction of free skin grafts following transposition of omental flap through a subcutaneous tunnel to the recipient bed. Macroscopic and microscopic evaluations were performed. Nineteen piglets were used. Two surgical wounds were created of each subject. The graft removed from the left side (LS) was placed on the right side (RS) without the omental flap in the graft-bed (control group-CG). On the LS, an omental flap was placed between the graft removed from the RS and the recipient bed (omentum group-OG). Macroscopic evaluations showed edema, which gradually decreased on both groups. Suture dehiscence was highest at day 10 compared to other days in both groups. The CG had a higher incidence of unvitalized tissue compared to OG, although no difference was found among days of postoperative evaluation. The presence of unvitalized tissue was seen on 32% on OG and 53% on CG. Microscopic evaluations revealed higher collagenization, reepithelization, keratinization and less swelling in the OG compared to CG. In conclusion, mesh skin grafts evolved satisfactorily in swine even in newly created bedding without granulation tissue, but with appropriate vascularization. The omentum flap provided better macroscopic and microscopic outcomes regarding graft integration
Keywords: Angiogenesis; Flap; Reconstructive surgery; Vascularization